Incomplete markets as correlated distortions - Tristany Armangue-Jubert; Davide Pietrobon; Alessandro Ruggieri (Lund University, School of Economics and Management, Department of Economics, 2025)
We argue that capital misallocation arises endogenously due to incomplete consumption insurance. We model risk-averse entrepreneurs with heterogeneous productivity who face idiosyncratic output shocks and choose how much capital to rent before uncertainty unfolds. We show that incomplete markets operate as correlated distortions, leading to a reallocation of capital from more to less productive firms relative to the complete markets benchmark. Using Portuguese administrative data, we document that capital misallocation is greater in locations and industries with higher output shock volatility, consistent with our framework. Leveraging the structure of the model, we show that completing insurance markets increases aggregate productivity and income by 64% and 97%, respectively
Keywords: E22; D61; L23; L26; 330; Insurance; volatility; misallocation; distortions; efficiency